Synthesis of Fuel Cell Membrane: Copolymerization of Styrene on ETFE Film by Grafted pre-Irradiation - Yohan, Yohan; Nur, Rifai M.; Hendrajaya, Lilik; Siradj, E. S. (Makara Journal of Technology, 2005)
Synthesis of Fuel Cell Membrane: Copolymerization of Styrene on ETFE Film by Grafted pre-Irradiation. Preirradiation Grafting styrene monomer on ETFE film has been prepared. Research has been performed by γ-ray radiation at various total dose from 2.5 – 12.5 kGy and various dose rate from 1.3 – 1.9 kGy/hour. Irradiated copolymer is then grafted by styrene monomer in various solvent: ethanol, 2-propanol, and toluene, various concentration from 20 – 70% volume, various temperature from 50 – 90oC, and various grafting time from 2 – 12 hours. The results showed that percent of grafting is increase with increase of total dose and decrease of rate dose. The optimum experiment conditions are obtained at total dose 10 kGy, dose rate 1,9 kGy/hour, 2-propanol solvent, 40% volume styrene, 4 hours grafting time, and 70oC grafting temperature.